Družbeni in kulturni kontekst mladostniške spolnosti z vidika študentov zdravstvenih ved - Kuzelj, Rebeka (Obzornik zdravstvene nege, 2025)
Introduction: Sexuality becomes more apparent with the onset of hormonal changes that characterise puberty and the change in the associated feelings and emotions. The information that adolescents receive often leads them to misconstrue and misinterpret adolescent sexuality. The aim of this study was to explore the social and cultural context of adolescent sexuality from the perspective of Health Sciences students.Methods: A qualitative research methodology using focus groups was employed. The purposive sample consisted of twelve students of Health Sciences (eight Nursing students and four Dietetics students), who were divided into three focus groups. The study took place in November 2022 at the participating institution. The data were analysed using content analysis.Results: Three thematic categories were identified: 1) student perspectives on adolescent sexuality, 2) societal influences on adolescent sexuality, and 3) knowledge acquisition from the perspective of adolescents. Student perspectives varied between age groups.Discussion and conclusion: The results reflecting the students’ perspectives suggest that adolescents engage in sexual activity from a very early age. Even if they are unaware of the potential risks at the time, they may be negatively affected later in life. Further research should be limited to Nursing students and expanded to other geographic areas of the country. The results could help to develop more effective sex education programmes.
Keywords: influence; intimate relationships; intimni odnosi; osebni vidik; personal aspect; sex education; spolna vzgoja; taboo; tabu; vpliv